Implementation of Transformative Sustainability Learning into Engineering Curricular - Yuliana Lavrysh (International Society of Philosophy and Cosmology, 2018)
Nowadays an engineering profession is the most promising in terms of sustainability. Yet, there is a question if higher educational establishments are ready and possess necessary resources to prepare graduates in a sufficient way to create a life-sustainable future. Therefore, universities recognize the education for sustainable development as an essential and timely process of engineering training. The paper presents the characteristics of transformative sustainability learning as a key factor of advanced life-learning engineering education. The analysis of theoretical background signifies that the transformative sustainability learning concept is based on the theory of person's transformations depending on such personality traits as the life experience, cognitive development, and critical reflection skills which foster personality changes towards sustainability. Thus, we can state that transformative sustainability learning (TSL) integrates such fields as transformative learning and Education for Sustainable Development and the combination impacts personal and societal transformations. This fact provides us with the opportunity to suggest the (TSL) concepts implementation into engineering educational process as an approach that enhances students' motivation to studying, understanding of sustainability issues and high order thinking skills. If students experience personality transformations, we can find out the pedagogical strategy attributed to these transformations. Having conducted interviews and observations the teaching process at the university, we outlined the most used TSL pedagogical strategies at technical university (placed-based, problem-based, enquiry and service learning) assessed their efficacy, found out the barriers to successful implementation and suggested recommendations to overcome the barriers. Our paper demonstrates potential of TSL implementation as it not only benefits for students but also enhances sustainability-related pedagogies transformative power.